What happens without population data? – The case of Ukraine - Molnár-Kovács, Dorottya (International Journal of Population Data Science, 2019)
According to the recommendation of the United Nations, national censuses should be taken at least every 10 years, and countries across Africa, Asia, the Americas and Europe are usually fairly disciplined in following this instruction. True, some European countries, including Denmark, Finland, the Netherlands or Iceland have in the last 30 years replaced traditional census enumerations with maintaining precise administrative registers, Ukraine however, is not one of these countries. With its last census carried out in 2001, the largest entirely European country is similar in this regard to countries such as Uzbekistan, Iraq or Sri Lanka. Because there is no reliable source of population data in Ukraine, estimations from different organizations and individuals vary considerably. In 2019 the UN estimates Ukraine’s population to be 43.8 M (the 2001 census result was 48.7 M), while according to the State Statistics Service of Ukraine (Grosstat), the number is 42.1 M (1.7 Million difference). The picture gets more complicated when we look at non-official estimates by politicians, non-governmental organizations, foreign press and further, otherwise serious sources: calculations that consider the proto-states of the Donbass region and Crimea to be part of Ukraine get results of 30-35 M people, while without these regions, Ukraine’s population is calculated to be somewhere between 20-26 million. Looking at these numbers the only apparent conclusion one can arrive at is the incredible degree of uncertainty. In a country where most families are in one way or another affected by permanent emigration, forced migration due to the war, seasonal work migration and the emigration of military-age men to avoid getting drafted, the population changes quickly. In my poster presentation I aim to showcase a number of different “creative” methods that official institutions in Ukraine use to get a picture of the actual population of the country and its regions, focusing mainly in Transcarpathia. These resourceful but often highly unreliable calculations include measuring bread consumption regionally and keeping count of the active mobile service users.